Mapping Analysis of Characteristics and Leadership Skills of Private Universities in Gorontalo City in the Era 4.0 - Siskawaty Yahya; Imam Mashudi; Djamila Podungge (Borong Newinera Publisher, 2020)
This research aims to see the mapping of the traits and skills of leadership of private universities in Gorontalo City in Era 4.0. This research method uses qualitative research with data analysis techniques using the Interactive Analysis model from Miles and Hiberman. The results of this study reveal that the quality of leadership that must be possessed by PTS in Gorontalo City is integrity, while for the skills that must be possessed by the Leaders of Private Universities (PTS) in Gorontalo City are technical skills. The results of this study. Based on the results of the study, it can be concluded that the nature of skills that is the factor for the success of the leadership of private universities in Gorontalo City in Era 4.0 is integrity. Meanwhile, leadership skills of private universities in Gorontalo City are more likely to be technical leadership. Thus, it is hoped that the Leadership must be able to adapt to the current conditions, in the era of all digitalization, must be able to take advantage of the available IT and it is necessary to maintain and maintain a noble character as a noble image of leadership.